STRUKTUR BIAYA INDUSTRI DAN PENGARUHNYA TERHADAP KINERJA INDUSTRI TEKSTIL DAN PRODUK TEKSTIL INDONESIA - Alla Asmara; Yeti Lis Purnamadewi; Anggi Meiri (School of Business, Bogor Agricultural University (SB-IPB), 2014)
The cost structure of textile and clothing industry will affect its performance. Therefore, the analysis of cost structure and its influence to the performance of textile and clothing industry is very important to do. The purpose of this study is to analyze the cost structure and factors that influence the performance of the textile and clothing industry. The analysis used in this research is descriptive and panel model analysis. The result shows that the share of domestic raw material cost is the largest in Indonesian textile and clothing industry cost structure, except for fiber industry where the share of imported raw material cost is the largest. Panel model analysis shows that industry structure, output value, and efficiency have a positive effect on performance (cost price margin/PCM) of textile and clothing industry. Meanwhile, the increases in costs (domestic raw material cost, imported raw material cost, labor cost, and fuel and lubricant cost) negatively affect the performance (PCM) of textile and clothing industry.Keywords: cost structure, performance analysis, panel model, price cost marginABSTRAKStruktur biaya industri tekstil dan produk tekstil (TPT) akan mempengaruhi kinerja industri tersebut. Oleh karena itu, analisis struktur biaya dan pengaruhnya terhadap kinerja industri TPT penting untuk dilakukan. Tujuan dari penelitian ini adalah untuk menganalisis struktur biaya industri TPT dan faktor-faktor yang mempengaruhi kinerja industri TPT. Analisis yang digunakan dalam penelitian ini adalah analisis deskriptif dan model panel. Hasil penelitian menunjukkan bahwa pangsa biaya bahan baku dalam negeri merupakan yang terbesar dalam struktur biaya industri TPT Indonesia, kecuali pada industri fiber dimana pangsa biaya bahan baku impor merupakan yang terbesar. Analisis model panel menunjukan bahwa struktur industri, nilai output, dan efisiensi berpengaruh positif terhadap kinerja (price cost margin/PCM) industri TPT. Sementara itu, peningkatan biaya-biaya (biaya bahan baku domestik, biaya bahan baku impor, biaya tenaga kerja, dan biaya bahan bakar dan pelumas) berpengaruh negatif terhadap kinerja (PCM) industri TPT.Kata kunci: struktur biaya, analisis kinerja, model panel, price cost margin